FIRST RECORD OF FOSSIL CYSTOPHORINAE (CARNIVORA, PHOCIDAE): MIDDLE MIOCENE SEALS FROM THE NORTHERN PARATETHYS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2013)
Despite a long history of phocid studies, no fossil members of the Subfamily Cystophorinae have ever been described. New fossil material from the Middle Sarmatian (11.2-12.3 Ma) in the Paratethyan Basin of Ukraine allows emended diagnoses and redescriptions to help clarify phylogenetic relationships within the Family Phocidae. After cladistic and morphological analyses of the material, a new genus ( Pachyphoca ) was erected, with two new species of extinct fossil true seals ( Pachyphoca ukrainica and Pachyphoca chapskii ), belonging to the Subfamily Cystophorinae. This new material shows exceptional pachyosteosclerotic bones, which is uncommon for the family as a whole. The new Miocene genus shares numerous characters with several Recent species of Cystophora and Mirounga , providing the first opportunity to study sexual dimorphism of limb bones and mandibles in the Subfamily Cystophorinae. Sexual dimorphism in postcranial bones and mandibles in living members of Cystophorinae is more obvious than in other representatives of true seals. Examination of anatomical traits demonstrated that both new species are more primitive and better adapted for terrestrial locomotion than any living representatives of Cystophorinae. The smaller Pachyphoca ukrainica is more adapted to terrestrial locomotion than its larger relative, P . chapskii . Phylogenetic analysis suggests that seals with 10 incisors (Phocinae) are more primitive than those with 8 (Monachinae), and that Monachinae are more primitive than seals with 6 incisors (Cystophorinae).These findings indicate that the Subfamily Cystophorinae includes not only elephant and hooded seals, but also the two new Middle Sarmatian pachyosteosclerotic seals.
Keywords: Phocidae; Cystophorinae; pachyosteosclerosis; sexual dimorphism; Miocene; Middle Sarmatian; Paratethys; Ukraine